Upaya Presiden Joko Widodo Menjadikan Indonesia sebagai Negara Ekonomi Digital Terbesar di Asia Tenggara - Sulaiman, Poppie Yolanda; Paksi, Arie Kusuma (Mahesa Research Center, 2022)
This study aims to find out how President Joko Widodo's efforts in realizing Indonesia become a country with the largest digital economy power in Southeast Asia with the potential that Indonesia has. The method used in this research is descriptive qualitative. The results of this study indicate that based on the mercantilism framework, the government seeks to make Indonesia the country with the largest digital economy power in Southeast Asia by utilizing digital economic activities in Indonesia to obtain or maximize profits from digital economic activities to meet the country's national interests. Efforts made by the government include pursuing technological developments by distributing digital infrastructure, mobilizing the UMKM sector in collaboration with MNCs, integrating the center with the National Data Center Development, preparing Funding Regulations for Digital Transformation, Preparing HR Needs and establishing a trade roadmap. Seeing these various efforts, the government has made use of existing technology and potential in the hope that it will increase competitiveness for the Indonesian economy.